PENGARUH MODEL PEMBELAJARAN PROBING-PROMPTING BERBANTUAN LEMBAR KERJA BERSTRUKTUR TERHADAP HASIL BELAJAR (Jurnal Inovasi Pendidikan Kimia, 2013)
This study aimed to know the influence of the use of a learning model Probing-prompting assisted by structured worksheet on learning outcomes in an high school especially in the Hydrocarbon and Petroleum. Sampling is done by using purposive sampling technique. In the experimental class, learning used Probing-prompting assisted by structured worksheet, while in classroom control used conventional methods. After being given a different treatment and after post test was done, it can be concluded that students' learning outcomes in class experiment is better than the control class, respectively 77 and 70. Based on the analysis of difference average learning outcomes, it obtained t count (4,074) t table (1,669), so it can be concluded that the average  of learning outcomes in experimental class is better than the control class. In the test mastery learning, mastery percentage of experimental class reached 91.18% while control class reached 59.38%. Test correlation obtained biserial coefficient of 0.5638. It can be concluded that the learning model of Probing-prompting assisted by structured worksheet have significant effect on student learning outcomes on Hydrocarbons and Petroleum subject with contribution of 32%.